Analysis on the understanding of environmental management practices among contractors in malaysia using rasch measurement model - Anisah Farhah Ahmad,; Haryanti Mohd Affandi,; Nurul Eizzaty Sohimi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The rapid development of construction industry in Malaysia has caused a significant impact on the environment and has resulted in increased demand for implementing environmental management practices. This study aimed to analyze the level of understanding on environmental management practices among contractors in Malaysia. A total of 47 contractors from all grades in Malaysia participated in this study. This study also used a 5-point Likert scale for the data collection process. Items in the questionnaire were analyzed using the Rasch Measurement Model to test the validity and reliability of the research instruments. The results showed that the item reliability value was 0.57 and the individual reliability value was 0.89. The value of the item separation index is 1.16 while the value of the individual separation index obtained is 2.78. Overall, person measure for construct of understanding level on environmental management practices ranged from +7.77 logit to -1.30 logit. For construct challenge faced by the contractor, the maximum value for person measure is +6.35 logit and the minimum measurement value is -0.97 logit. For the last construct which is the impact of environmental management practices on the environment, the value of person measure is +8.27 logit to -1.62 logit. Through item suitability analysis, there are some items that need to be dropped or harmonized as they not meet the requirements in one of the Outfit MNSQ and Outfit ZSTD ranges. The Rasch Measurement Model has identified that most contractors in Malaysia still have a moderate level of understanding on environmental management practices. The findings obtained at the end of this study are significant so that these environmental management practices remain practiced by contractors to maintain sustainable development in future.